CHALLENGES AND SOLUTIONS IN LEARNING ENGLISH AS A SECOND LANGUAGE (ESL) (Modern education and development, 2024)
Learning English as a Second Language (ESL) poses significant challenges for non-native speakers, impacting their ability to acquire proficiency in the language. This article explores the key obstacles faced by ESL learners, including difficulties with pronunciation, grammar, vocabulary, listening comprehension, cultural differences, motivation, and limited exposure to English. For each challenge, practical solutions are provided, emphasizing the importance of tailored language instruction, immersive experiences, and psychological support. Through a combination of focused teaching strategies, technology-assisted learning tools, and cultural immersion, learners can overcome these barriers and progress toward greater language fluency. The article highlights the need for educators and learners to adopt an integrated approach to ESL learning, ensuring both linguistic and socio-cultural competence.